The Effect of the Experimental Method on Students' Science Learning Outcomes on the Topic of Force Altering an Object's Motion in Grade IV of SDN 4 Dawuan - Tutut Elisa (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to determine students' science learning outcomes before the implementation of the experiment method on the topic of force affecting the motion of objects, to determine students' science learning outcomes after the implementation of the experiment method, and to determine the effect of the experiment method on the science learning outcomes of fourth-grade students at SDN 4 Dawuan. The study employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 35 students selected through a saturated sampling technique. Data were collected through learning outcome tests administered before and after the implementation of the experiment method. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Paired Sample t-Test, and N-Gain analysis. The results showed that students' learning outcomes before the implementation of the experiment method were still low, with a mean pretest score of 4.34. Students' learning outcomes improved after the implementation of the experiment method, as indicated by a mean posttest score of 6.14 and an increase in the number of students who achieved learning mastery. The hypothesis test showed a significance value of 0.000 < 0.05 and an N-Gain score of 0.3828, which was categorized as moderate. The experiment method had a positive and significant effect on students' science learning outcomes.